Chlorogenic acid improves glucose tolerance, lipid metabolism, inflammation and microbiota composition in diabetic db/db mice - Yan, Yongwang; Li, Qing; Shen, Ling; Guo, Kangxiao; Zhou, Xu (Frontiers in Endocrinology, 2022)
Introduction Chronic and acute chlorogenic acid (CGA) can improve glucose tolerance (GT) and insulin sensitivity (IS). However, whether acute administration of CGA has beneficial effects on hepatic lipid metabolism and cecal microbiota composition remains unclear. Methods In the current study, diabetic db/db mice were administered CGA or metformin, and db/m mice were used as controls to explore the effects of CGA on hepatic lipid metabolism, including fatty acid oxidation and transportation and triglyceride (TG) lipolysis and synthesis. Moreover, alterations in the inflammatory response and oxidative stress in the liver and gut microbe composition were evaluated. Results The results showed that CGA decreased body weight and improved glucose tolerance and insulin resistance, and these effects were similar to those of metformin. CGA decreased hepatic lipid content by increasing the expression of CPT1a (carnitine palmitoyltransferase 1a), ACOX1 (Acyl-CoA oxidase 1), ATGL (adipose triglyceride lipase), and HSL (hormone-sensitive lipase) and decreasing that of MGAT1 (monoacylglycerol O-acyltransferase 1), DGAT1 (diacylglycerol O-acyltransferase), DGAT2, CD36, and FATP4 (fatty acid transport protein 4). Additionally, CGA restored the expression of inflammatory genes, including TNF-α (tumor necrosis factor-alpha), IL-1β (interleukin-1beta), IL-6, and IL-10, and genes encoding antioxidant enzymes, including SOD1 (superoxide dismutases 1), SOD2 (superoxide dismutases 2), and GPX1 (glutathione peroxidase 1). Furthermore, CGA improved the bacterial alpha and beta diversity in the cecum. Moreover, CGA recovered the abundance of the phylum Bacteroidetes and the genera Lactobacillus, Blautia, and Enterococcus. Discussion CGA can improve the antidiabetic effects, and microbes may critically mediate these beneficial effects.